Títulos Valores y Derecho Mercantil - Zegarra Mulánovich, Álvaro (Revista de Derecho, 2019)
In this article two questions are met in connection with the systematics of thegeneral theory of commercial papers or negotiable instruments. First, the questionis considered of wether that theory pertains, as a general private Law doctrine, tothe General Private Law (or “Derecho Civil”) or to the Commercial Law (“DerechoMercantil”). Then the article deals with the problem of wether the same generaltheory of commercial papers is a part of Property Law or of the Contract Law. In bothcases, the argumentation leads to a preference for the second alternative.
Keywords: Negotiable instrumen; Commercial Law,; General private Law; Law of godos; Contract Law